Functional impairment of circulating FcεRI+ monocytes and myeloid dendritic cells in hepatocellular carcinoma and cholangiocarcinoma patients - Martín-Sierra, Carmen (2019)
Background Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) represent the most common primary liver malignancies whose outcome is influenced by the immune response. Methods In this study, we have functionally characterized, by flow cytometry, circulating myeloid dendritic cells (mDCs) and FcεRI+ monocytes in a group of healthy individuals (n = 10) and in a group of patients with HCC (n = 19) and CCA (n = 8), at the time point of the surgical resection (T0) and once the patient had recovered from surgery (T1). Moreover, we proceeded to a more in depth phenotypic characterization of the FcεRI+ monocyte subpopulation. Results A significant decrease in the frequency of TNFα producing FcεRI+ monocytes and mDCs in HCC and CCA patients when compared to the group of healthy individuals was observed, and a close association between FcεRI+ monocytes and mDCs dysfunction was identified. In addition, the phenotypic characteristics of FcεRI+ monocytes from healthy individuals strongly suggest that this population drives to mDCs, which matches with the fact that both populations are functionally affected. Conclusions The frequency and the function of circulating mDCs and FcεRI+ monocytes are affected in both HCC and CCA patients, and FcεRI+ monocytes could represent those fated to become mDCs.